1993
DOI: 10.1159/000111333
|View full text |Cite
|
Sign up to set email alerts
|

Development of Enzymes of Energy Metabolism in the Neonatal Mammalian Brain

Abstract: The metabolic capability for the complete oxidation of glucose, i.e. aerobic glycolysis, is highly developed in the brains of neurologically mature (precocial) species at birth, whereas this activity is severely limited in the brains of neurologically immature (non-precocial) species such as the rat and human. The latter utilize a mixture of glucose and ketone bodies for synthetic and energetic activities and the advent of neurological competence associated with the capability for complete dependence on and ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 15 publications
(26 reference statements)
1
26
0
Order By: Relevance
“…However, when mitochondria are inhibited, ATP production by glycolysis is increased, by the Pasteur effect, by a factor of 4 -5 because of increased activity of phosphofructokinase, hexokinase, and glucose transport (Lowry et al, 1964;Drewes and Gilboe, 1973;Depré et al, 1998), and thus there should be much more ATP production than is normally generated by glycolysis. Although P12 animals may rely less on oxidative phosphorylation than older animals and maintain membrane potentials and neuronal excitability through glycolysis alone (Clark et al, 1993;Nabetani et al, 1995), we found identical results in older (P28) rat slices when the oxidative phosphorylation system is mature; i.e., external glucose was sufficient to prevent the AD.…”
Section: External Glucose Prevents the Ad From Occurringsupporting
confidence: 64%
See 2 more Smart Citations
“…However, when mitochondria are inhibited, ATP production by glycolysis is increased, by the Pasteur effect, by a factor of 4 -5 because of increased activity of phosphofructokinase, hexokinase, and glucose transport (Lowry et al, 1964;Drewes and Gilboe, 1973;Depré et al, 1998), and thus there should be much more ATP production than is normally generated by glycolysis. Although P12 animals may rely less on oxidative phosphorylation than older animals and maintain membrane potentials and neuronal excitability through glycolysis alone (Clark et al, 1993;Nabetani et al, 1995), we found identical results in older (P28) rat slices when the oxidative phosphorylation system is mature; i.e., external glucose was sufficient to prevent the AD.…”
Section: External Glucose Prevents the Ad From Occurringsupporting
confidence: 64%
“…In case the protective effect of external glucose was caused by ATP production in the young (P12) animals used here being more dependent on glycolysis than is the case in older animals (Clark et al, 1993;Nabetani et al, 1995), we repeated this experiment in slices from P28 rats (in which enzymes of aerobic metabolism are at adult levels) (Clark et al, 1993). The same abolition of the AD by 10 mM glucose was obtained: in the absence of glucose, the latency to the AD in N 2 -bubbled solution containing rotenone, antimycin, and iodoacetate was ϳ4 min (230 Ϯ 8 s; n ϭ 7; i.e., approximately one-half of the latency seen in P12 slices), but in the presence of 10 mM glucose and in the absence of iodoacetate, no AD was seen for Ͼ1 h in six cells (recording time with no AD was 3 h for one cell and had a mean value of 4890 Ϯ 1230 s) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of the enzymes involved in the metabolism of glucose [3][4][5][6][7], ketone bodies [7,8], and fatty acids [9,10] have all been measured. These data in combination with measured arteriovenous differences in concentration of glucose, lactate and ketone bodies in vivo have demonstrated the fact that the neonatal brain unlike the adult brain is not solely dependant on glucose as its major source of energy, but can obtain a significant proportion of its energy requirements from the metabolism of ketone bod ies (2,11], lactate (12,13] and in the case of astrocytes also from free fatty acids [ 14].…”
Section: Introductionmentioning
confidence: 77%
“…Therefore, depolarizing actions of GABA are not attributable to the absence of DL-BHB or lactate/pyruvate in the ACSF. dehydrogenase that metabolize it (Page et al, 1971;De Vivo et al, 1975;Leong and Clark, 1984;Bilger and Nehlig, 1991;Clark et al, 1993), peak during development well after the GABA shift. Fatty acid oxidation supports gluconeogenesis (Pégorier et al, 1977), and ketosis acts to "spare glucose for the emergence of audition, vision and more integrated behavior whose appearance during brain maturation seems to critically relate upon active glucose supply" (Nehlig, 2004).…”
Section: Discussionmentioning
confidence: 99%